ANALYSIS OF NOTARY CRIMINAL RESPONSIBILITY IN RUNNING THEIR PROFESSION INDICATES AGAINST CRIMINAL LAW (Study on Decision Case Number 40 / Pid.B / 2016 / PN.Btl) - Adelsa Anggie Fawzia NP; Suryawan Raharjo (Kajian Hasil Penelitian Hukum, 2021)
The responsibility of the Notary is very large in providing legal certainty to the public, because the Notary is given the authority to make a means of proof in the form of an authentic deed to guarantee legal order and protection for interested parties and society as a whole. But in reality, there are notaries who make deeds of unlawful acts that can harm other people. One of them is the case that has been decided by the Bantul District Court Number 40 / Pid.B / 2016 / PN.Btl.This type of research is juridical empirical. Data collection techniques through interviews and literature study. The data analysis technique used descriptive qualitative.The results of the study concluded: First, the judicial process mechanism against the Notary must obtain approval from the local MKN. This is in accordance with Article 66 Article (1) of Law Number 2 of 2014, namely for the benefit of the judicial process, investigators, public prosecutors, or judges with the approval of the competent Regional Supervisory Council (MPD). Second, the basis for consideration used by judges to try Notaries who are involved in a criminal offense is Article 374 of the Criminal Code, which has the following elements: (a) Whoever; (b) Intentionally and illegally possessing property, wholly or partly belonging to another person, but which is in his control not because of a crime; and (c) What is done by a person whose control of property is due to a work relationship or because of his search or because I get paid for it. Third, the responsibility of a notary is attached to his position, unless it is proven that due to the intention of the Notary, so that the Notary is subject to criminal elements such as embezzlement by the person who controls the item because of his position, so the responsibility of the Notary is subjective or personal.